2003
DOI: 10.1016/s1099-5129(03)00077-1
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam or midazolam for external DC cardioversion (The DORM Study)

Abstract: Physician-led cardioversion of atrial arrhythmias using intravenous sedation is effective and well tolerated. Sedation with diazepam was associated with fewer minor adverse events and a quicker recovery time than midazolam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…In comparative studies with diazepam in several procedures, midazolam proved more effective at inducing rapid sedation. 16,[18][19][20] Midazolam is known to be rapidly absorbed and the onset of action is, therefore, faster than that of diazepam and its effects are expected to occur sooner than those of diazepam. In addition, the dose of both drugs to reach adequate sedation was similar.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In comparative studies with diazepam in several procedures, midazolam proved more effective at inducing rapid sedation. 16,[18][19][20] Midazolam is known to be rapidly absorbed and the onset of action is, therefore, faster than that of diazepam and its effects are expected to occur sooner than those of diazepam. In addition, the dose of both drugs to reach adequate sedation was similar.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] It has repeatedly been shown that physician-led sedation using the benzodiazepine diazepam is also safe and has a positive impact on patient acceptability of the procedure. 15,16 In several countries, benzodiazepines are still the main drug of choice for procedures instead of using newer, rapidly acting, anesthetics, largely driven by cost concerns. 16 In the Santa Casa Hospital Complex (seven hospitals and eight ICUs), midazolam is the drug most used -and frequently solely used -for sedation in procedures like upper endoscopy, cardioversion or intubation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations